Anthropological commentary on COVID-19 vaccine hesitancy: a Bangladesh perspective - Chowdhury, Shafquat H.; Mithila, Turna T.; Tolchard, Barry (International Journal Of Community Medicine And Public Health, 2023)
From a Bangladeshi perspective, this commentary discusses the problem of vaccine hesitancy (VH) and its outcome within the Bangladeshi population, including minority ethnic groups. Relatively low vaccination rates among the Bangladeshi population are associated with people’s social and economic conditions and are the focus of public health activities and regulations in the broader region. This short commentary uses examples from minority ethnic groups in Bangladesh, including tribal groups, to address three main objectives. First, the need to understand better population management over vaccine outcomes and efforts to minimise overlooking the minority ethnic population. This understanding can assist in overcoming the reluctance of VH among the Bangladeshi people in a trusted and sustainable manner. Secondly, being part of a more comprehensive rethinking of public health interactions with minority ethnic populations, this commentary promotes exploring the epidemiological context of the VH rate among the Bangladeshi people. This paper proposes strengthening the credibility of vaccinations rather than recommending measures to encourage vaccine coverage in Bangladesh. Finally, it emphasises how crucial it is to interact with minority ethnic groups in the context of the new public health preparation strategies following Bangladeshi VH concepts. This article examines survey data and secondary information. PubMed and Google Scholar identified literature reviews to support the proof for exploring the possible concerns regarding VH among the Bangladeshi population.